Pengaruh Pemberian Kopi Terhadap Kelelahan Atlet Pabsi Pusat Pendidikan Dan Latihan Mahasiswa - Melissa, Mia; Zamzami; Mawardi; Edi Azwar; insan Nuhari (Jurnal Serambi Ilmu, 2025)
Global changes have reinforced the importance of English in the international economy and job market. Vocational high school students, with their emphasis on skills and work readiness, often face unique challenges in learning English, particularly in speaking. Speaking anxiety emerges as a major barrier, hindering fluency, lowering confidence, and limiting practice opportunities, which in turn affects their overall speaking development. This study aimed to investigate the levels of English-speaking anxiety and its contributing factors among vocational students at SMK PGRI 4 Pasuruan. Employing a quantitative method with a cross-sectional survey design, data were gathered from 99 students in Grades X and XI using a questionnaire adapted from the Foreign Language Classroom Anxiety Scale (FLCAS). The responses were analyzed with SPSS version 27 through descriptive statistics such as mean, percentage, and standard deviation. The findings revealed that 72.73% of students experienced moderate speaking anxiety, 14.14% showed high anxiety, and 13.13% reported low anxiety. The dominant factor was internal or psychological aspects (Mean = 33.74), including lack of self-confidence, fear of making mistakes, negative self-perception, and past negative experiences. Overall, students’ speaking anxiety was categorized as moderate. This study suggests that English teachers should foster supportive classroom environments, apply communicative teaching strategies, provide constructive and private feedback, and incorporate vocational-related speaking tasks to increase students’ confidence and workplace readiness.